PENGARUH TERAPI LIFE REVIEW TERHADAP PENURUNAN TINGKAT DEPRESI LANSIA DI PANTI WERDHA RUMAH BAHAGIA BINTAN KEPULAUAN RIAU - Utari Christya Wardhani; Sri Muharni; Kurnia Izzati (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
Depression can be affected by the elderly in the end of their life. Depression is not a normal aging process, but psychosocial problem that can be overcome. Aswanira and Vausta (2015) explained that the prevalence of depression ranged from 10-15% in the elderly in the community, 11-45% of the elderly who need hospitalizationt, and up to 50% of the elderly who live in nursing home. One therapeutic modality for reducing depression is Life Review Therapy. Life Review Therapy is the most suitable therapy for the elderly because in general the elderly often tell their life experiences. The purpose of this study was to determine the effect of life review therapy on decrease the depression level for elderly. This study was a Quasi Experimental design. Data were analyzed by using Paired Sample t-Test. Sample of this study were 15 elderly respondents with Purposive Sampling method. The result of this study have shown that before life review therapy more than half of elderly (60%) suffer medium depression, after life review therapy all of the elderly (100%) having the decrease of depression level become normal. The conclusion of data analyse have shown that p-value 0,000 (p=<0,05). There is an effect of life review therapy on decrease the depression level for elderly. It is expected that life review therapy can be applied as a life nursing alternative action to overcome the depression towards the elderly.